Quality of life: review on an approach integrating Maqasid al-Shariah - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah; Abdullah, Alias (2016)
Quality of life is one of the indicators to measure a nation’s development status, economic growth and political stability.. Previous studies suggested that modernisation and globalisation has influenced the development of various techniques or parameters to measure the quality of life of the people. The social, economic, quantitative, qualitative or subjective well-being indicators have been developed to define and measure quality of life including through assessing people’s reactions to their lives and societies. However, there is also a holistic approach to measure quality of life form religious perspectives. A more holistic and inclusive concept to represent the new quality of life model that integrates the physical/material, intellectual and spiritual dimensions of human beings need to be formulated or studied in order to make the study on quality of life more comprehensive. This paper attempts to review the literature of quality of life in relation to the Islamic principle of. The study on Maqasid al-Shariah in relation to conventional theory of quality of life is essential to Malaysian as majority of the population (60% of the population) is Muslim. Finding from the study is hoped to be beneficial to the stakeholders and policy makers in developing policies and strategies that able to enhance the quality of life of Malaysian